Arm lymphoscintigraphy after axillary lymph node dissection or sentinel lymph node biopsy in breast cancer - Sarri, Almir José; Dias, Rogério [UNESP]; Laurienzo, Carla Elaine; Gonçalves, Mônica Carboni Pereira; Dias, Daniel Spadoto [UNESP]; Moriguchi, Sonia Marta [UNESP] (Taylor & Francis, 2017)
Purpose: Compare the lymphatic flow in the arm after breast cancer surgery and axillary lymph node dissection (ALND) versus sentinel lymph node biopsy (SLNB) using lymphoscintigraphy (LS). Patients and methods: A cross-sectional study with 39 women >18 years who underwent surgical treatment for unilateral breast cancer and manipulation of the axillary lymph node chain through either ALND or SLNB, with subsequent comparison of the lymphatic flow of the arm by LS. The variables analyzed were the area reached by the lymphatic flow in the upper limb and the sites and number of lymph nodes identified in the ALND or SLNB groups visualized in the three phases of LS acquisition (immediate dynamic and static images, delayed scan images). For all analyses, the level of significance was set at 5%. Results: There was a significant difference between the ALND and SLNB groups, with predominant visualization of lymphatic flow and/or lymph nodes in the arm and axilla (P=0.01) and extra-axillary lymph nodes (P<0.01) in the ALND group. There was no significant difference in the total number of lymph nodes identified between the two groups. However, there was a significant difference in the distribution of lymph nodes in these groups. The cubital lymph node was more often visualized in the immediate dynamic images in the ALND group (P=0.004), while the axillary lymph nodes were more often identified in the delayed scan images of the SLNB group (P<0.01). The deltopectoral lymph node was only identified in the ALND group, but with no significant difference. Conclusion: The lymphatic flow from the axilla was redirected to alternative extra-axillary routes in the ALND group.
Keywords: Breast neoplasms; Lymphadenectomy; Lymphatic diseases; Radionuclide imaging